Thymus’ gland. Clinical, morphological and functional aspects. - Dunia Reyes Hernández; Mayra Gil León; Galia Ivis Pérez Rumbaut; Carmen Niurka Piña Loyola (Medisur)
This article contains an updated review about the thymus making references to aspects related to its embriologic development, functions, morphology, and hormones the thymus produces and its principal effects, as well as the thymus; involution and its structural alterations, with the aim of offering enough information that allows the comprehension of the functional importance of this organ which has been considered as a non-functional organ for a long time.